EXPERIMENTAL STUDY OF INCONGRUENT EVAPORATION KINETICS OF ENSTATITE IN VACUUM AND IN HYDROGEN GAS - Tachibana S.; Tsuchiyama A.; Nagahara H. (My University, 2002)
Variations in bulk Mg/Si ratios in the various groups of chondritic meteorites indicate that Mg/Si fractionation occurred in the primitive solar nebula. Enstatite (MgSiO3) evaporates incongruently forming forsterite (Mg2SiO4) as an evaporation residue; therefore, evaporation of enstatite produces Mg/Si variations in solid (Mg-rich) and gas (Si-rich) and must be considered as a probable process responsible for Mg/Si fractionation recorded in chondrites. To understand the evaporation kinetics of enstatite, incongruent evaporation experiments on enstatite single crystals have been carried out in vacuum and in hydrogen gas at temperatures of 1300 to 1500°C. A polycrystalline forsterite layer is formed on the surface of enstatite by preferential evaporation of the SiO2 component, both in vacuum and in hydrogen gas. The thickness of the forsterite layer in vacuum increases with time in the early stage of evaporation and later the thickness of the forsterite layer remains constant (several microns). This is due to the change in the rate limiting process from surface reaction plus nucleation and growth to diffusion in the surface forsterite layer. The activation energy of the diffusion-controlled evaporation rate constant of enstatite is 457 (+/-58) kJ/mol. A thinner forsterite layer is formed on the surface of enstatite in hydrogen gas than in vacuum. Evaporation of enstatite in hydrogen gas is also considered to be controlled by diffusion of ions through the forsterite layer. The thin forsterite layer formed in hydrogen gas is ascribed to the enhanced evaporation rate of forsterite in the presence of hydrogen gas.The results are applied to incongruent evaporation under the solar nebular conditions. The steady thickness of the forsterite of nebular pressure-temperature conditions is estimated to be submicron because of the enhanced evaporation rate of forsterite under hydrogen-rich nebular conditions if evaporated gases are taken away immediately and no back reaction occurs (an open system). Because enstatite grains in the solar nebula would be comparable to the estimated steady thickness of forsterite, evaporation of such enstatite grains under kinetic conditions could play an important role in producing variations in Mg/Si ratios between solid and gas in the solar nebula.